Conjugacy of two types of phenotypic variability of small-leaved linden - S. G. Baranov; I. E. Zykov; D. D. Kuznetsova (Вавиловский журнал генетики и селекции)
The properties of five bilaterally symmetrical features of the leaf blades of the small-leaved linden (Tilia cordata Mill.) in four populations of the Moscow Region in 2014–2017 were studied. The angle trait was excluded, because it possessed the property of directional asymmetry. Instead, a new linear trait was used: the distance between the base of the second vein of the first order and the base of the first vein of the second order on the first vein of the first order. The population difference in fluctuating asymmetry (FA) was found only in the first two traits (leaf width and distance between the bases of the first vein of the first order and the second vein of the second order). The largest value of FA was in the urban environment, the smallest was in the rural areas. A weak negative correlation was obtained between the magnitude of linear characteristics and the value of FA, as well as a weak positive correlation relationship between the values of FA in five traits. The first trait had the highest fluctuation variability, and the second one had the highest plastic variability. The regression dependence of the fluctuation variability on the plastic variability (b1 = 0.25, p <0.05) and the dependence of these two types of variability on the interaction of the factors “year” and “site of sampling” were revealed. Thus, the conclusion was made about the conjugacy of two types of variability: fluctuation and plastic. According to the authors, asynchronous growth, competition for light in conditions of high solar activity in 2014–2016 compared to the abnormal wet summer of 2017 led to an increase in FA due to destabilization of mechanisms of growth and regulation of gene expression, which contributed to a decrease in the stability of development. The increase in FA and the decrease in the developmental stability in urban ambient in 2016 could be due to: a)an intensive flow of vehicles in spring and summer, b) a high level of groundwater in this part of the city and c) increased hydrolytic acidity of the soil.